2015
DOI: 10.5152/akd.2015.5922
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability improvement in children using transcatheter atrial septal defect closure

Abstract: Objective:We evaluated autonomic behavior by examining heart rate variability (HRV) in the time domain and frequency domain in pediatric patients who underwent transcatheter closure of atrial septal defect (ASD).Methods:A prospective study design was used. Holter ECG was performed in a control group of 30 healthy subjects and a group of 47 patients who underwent transcatheter ASD closure. ECG was taken one day before, one day after, and six months after the procedure to evaluate changes in the time domain [SDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Third, another issue to be considered is the effect of nonlinear and non-stationary processes that have necessarily to be present in these critically ill patients [22,23,33], and that can be overcome using appropriate methods for the analysis of HRV indices, as those used in this study. Fourth and finally, the inclusion for the spectral analysis of HRV indices of the very high frequency range (0.4 -0.6 Hz), that has been not extensively studied, but that has shown evidences of pathophysiologic interest in the last years [70,71,[99][100][101]. All these issues were considered in our study and possibly are associated to better results, so we recommend them for later use in this field.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Third, another issue to be considered is the effect of nonlinear and non-stationary processes that have necessarily to be present in these critically ill patients [22,23,33], and that can be overcome using appropriate methods for the analysis of HRV indices, as those used in this study. Fourth and finally, the inclusion for the spectral analysis of HRV indices of the very high frequency range (0.4 -0.6 Hz), that has been not extensively studied, but that has shown evidences of pathophysiologic interest in the last years [70,71,[99][100][101]. All these issues were considered in our study and possibly are associated to better results, so we recommend them for later use in this field.…”
Section: Discussionmentioning
confidence: 96%
“…Later, other authors [125,126] demonstrated that the VHF peaks were not artifactual, and that its presence could serve as a diagnostic test for vagal denervation, and even classified the VHF peaks into two types associated to possible different pathophysiologic significance [127]. Other authors have reported differences of VHF spectral measures between patients with cardiologic disturbances and healthy controls [99,100]. Recently [101] we have shown, using three spectral methods, including the Hilbert- Considering the whole group of patients, the observed proportion was of 10 in 47 patients (21.2 %).…”
Section: Very High Frequency Oscillations Of Patients In Comamentioning
confidence: 99%
“…It has been shown that HRV is reduced in children with ASD [ 4 , 5 ]. Surgery or transcatheter closure can improve HRV in pediatric patients [ 6 8 ]. However, there is not much research on HRV in adult patients with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Özyılmaz et al 28 in their study observed children with ASD before and after the endovascular treatment. The criteria for inclusion in the study were: ASD of more than according to ECHO data and the possibility of catheter closure of the defect.…”
Section: Features Of Hrv Dynamics After Surgical and Endovascular Cormentioning
confidence: 99%